Cartographic systems and non-linguistic inference. (2nd April 2016) - Aguilera, Mariela
Abstract: It is often assumed that the capability to make inferences requires language. Against this assumption, I claim that inferential abilities do not necessarily require a language. On the contrary, certain cartographic systems could be used to explain some forms of inferences, and they are capable of warranting rational relations between contents they represent. By arguing that certain maps, as well as sentences, are adequate for inferential processes, I do not mean to neglect that there are important differences between maps and sentences. Instead, the purpose of this paper is to highlight interesting distinctions that might affect the way that cartographic thinking works.